A GUARANTEED PURSUIT TIME IN A DIFFERENTIAL GAME IN HILBERT SPACE - Ibragimov, Gafurjan; Waziri, Usman; Alias, Idham Arif; Ibrahim, Zarina Bibi (Malaysian Journal of Science (MJS), 2019)
We study a pursuit differential game problem of one pursuer and one evader in the Hilbert space . The differential game is described by an infinite number of first-order 2-systems of linear differential equations. The control functions of players are subjected to integral constraints. A game is started from the given initial position . It is given another point in the space . If the state of the infinite system coincides with the point at some time, then pursuit is considered completed. Our purpose is to obtain an equation to find a guaranteed pursuit time and construct a strategy for the pursuer.